THE INFLUENCE OF LONG-TERM THERAPY WITH PERINDOPRIL ON THE HEART INOTROPIC FUNCTION IN PATIENTS WITH CHRONIC POSTINFARCTION ANEURISM - I. G. Fomina; N. A. Galanina; Z. O. Georgadze; N. E. Gaidamakina (Рациональная фармакотерапия в кардиологии)
Aim. To study the influence of long-term therapy with perindopril on the heart inotropic function in patients with chronic postinfarction aneurism. Material and methods. 21 patients suffering ischemic heart disease with postinfarction cardiosclerosis, chronic aneurism of left ventricle and chronic heart failure of functional class III-IV according to NYHA were observed. All patients took perindopril, 2-4 mg daily. Before and after 6 months of therapy myocardial contractile function of left and right ventricles was studied by balanced radioventriculography with segmental and phase analysis of histogram. Results. In patients with chronic postinfarction aneurism significant structural and functional abnormalities were revealed: reduction of left ventricular ejection fraction up to 17,8 ± 3,2 %, the same for right ventricular up to 22,1±4,4 %, their considerable dilation with reduction of filling and expulsion velocity. After 6 months of therapy with  perindopril  improvement of clinic status of patients, tendency towards  increase of both ventricles general ejection fraction, enlargement of maximal filling velocity and filling velocity during 1/3 of diastole as well as tendency to reduction of both ventricles end diastolic and systolic volumes were registered. In left ventricle there were normokinetic zones in 35 (21%) segments, hypokinetic zones in 24 (14%), akinetic zones in 54 (32%) and dyskinetic zones in 17 (10%) segments. In right ventricle there were normokinetic zones in 45 (27%) segments, hypokinetic zones in 62(37%), akinetic zones in 54 (32%) and dyskinetic zones in 7 (4%) segments. After 6 months of therapy with perindopril tendency towards improvement of local myocardial contractility was registered. Conclusion. In patients with chronic postinfarction aneurism deterioration of general and local myocardial contractility were registered. Accurate link between left ventricle local myocardial contractility and localization of aneurism were not revealed. After 6 months of therapy with perindopril tendency towards improvement of general and local myocardial contractility of both ventricles was registered.